Study of Clinical Profile and Immediate Outcome of Congenital Heart Disease in Neonates at a Tertiary Care Hospital in India: A Single Center experience - Farzana Farzana; Leslie Lewis; Arvind Bishnoi; Apurv Barche; Gunjan Banga; Anand Patil; Jayashree Purkayastha (Iranian Journal of Neonatology, 2025)
Background: Data on congenital heart diseases in neonates, especially critical congenital heart disease, varies worldwide. Developing countries have higher mortality than developed countries. To study the clinical profile of congenital heart diseases in neonates.Methods: Prospective observational study. Neonates admitted to a tertiary care hospital with congenital heart disease. Clinical details, investigations, and management of neonates admitted to a tertiary care hospital were studied prospectively.Results: Among the study neonates, 60% had acyanotic heart disease, the most common being ASD, while 40% had cyanotic heart disease, the most common being TGA—outborn cases comprised 60% of the total neonates. The most common presenting features were fast breathing and cyanosis; the most common clinical sign was murmur(59%). Among the study neonates, 15 cases had low calcium levels. Definitive surgery was done in 21 neonates, of which 7 succumbed. The staged repair was done in 9 neonates, of which 2 succumbed. Of 12 TGA cases,10 underwent definitive repair, and 7 did well at follow-up. Among the 10 TOF babies, 6 underwent staged repair. Out of the 7 cases of CoA, 6 underwent definitive surgery, and 1 expired. Among Critical CHD, mortality was 23.3%.Conclusion: The most common cyanotic heart disease was ASD, and the most common cyanotic heart disease was TGA. Surgery was done in 30 cases, out of which 9 succumbed, and mortality among surgical cases was 30%. At follow up TGA  cases with definitive surgeries were doing well. Mortality was lower compared to other studies in India. Hypocalcemia was observed in 16.6% of the CHD cases, which needs to be studied in the future.